Recurrent Lumbar Disc Herniation: A Review. Issue 2 (April 2019) - Shepard, Nicholas; Cho, Woojin
Study Design: Narrative review. Objectives: To identify the risk factors and surgical management for recurrent lumbar disc herniation using a systematic review of available evidence. Methods: We conducted a review of PubMed, MEDLINE, OVID, and Cochrane Library databases using search terms identifying recurrent lumbar disc herniation and risk factors or surgical management. Abstracts of all identified articles were reviewed. Detailed information from articles with levels I to IV evidence was extracted and synthesized. Results: There is intermediate levels III to IV evidence detailing perioperative risk factors and the optimal surgical technique for recurrent lumbar disc herniations. Conclusions: Multiple risk factors including smoking, diabetes mellitus, obesity, intraoperative technique, and biomechanical factors may contribute to the development of recurrent disc disease. There is widespread variation regarding optimal surgical management for recurrent herniation, which often include revision discectomies with or without fusion via open and minimally invasive techniques.